Inhibition of prolyl hydroxylases increases hepatic insulin and decreases glucagon sensitivity by an HIF-2α-dependent mechanism - Matthew Riopel; Jae-Su Moon; Gautam K. Bandyopadhyay; Seohee You; Kevin Lam; Xiao Liu; Tatiana Kisseleva; David Brenner; Yun Sok Lee (Elsevier, 2020)
Objective: Recent evidence indicates that inhibition of prolyl hydroxylase domain (PHD) proteins can exert beneficial effects to improve metabolic abnormalities in mice and humans. However, the underlying mechanisms are not clearly understood. This study was designed to address this question. Methods: A pan-PHD inhibitor compound was injected into WT and liver-specific hypoxia-inducible factor (HIF)-2α KO mice, after onset of obesity and glucose intolerance, and changes in glucose and glucagon tolerance were measured. Tissue-specific changes in basal glucose flux and insulin sensitivity were also measured by hyperinsulinemic euglycemic clamp studies. Molecular and cellular mechanisms were assessed in normal and type 2 diabetic human hepatocytes, as well as in mouse hepatocytes. Results: Administration of a PHD inhibitor compound (PHDi) after the onset of obesity and insulin resistance improved glycemic control by increasing insulin and decreasing glucagon sensitivity in mice, independent of body weight change. Hyperinsulinemic euglycemic clamp studies revealed that these effects of PHDi treatment were mainly due to decreased basal hepatic glucose output and increased liver insulin sensitivity. Hepatocyte-specific deletion of HIF-2α markedly attenuated these effects of PHDi treatment, showing PHDi effects are HIF-2α dependent. At the molecular level, HIF-2α induced increased Irs2 and cyclic AMP-specific phosphodiesterase gene expression, leading to increased and decreased insulin and glucagon signaling, respectively. These effects of PHDi treatment were conserved in human and mouse hepatocytes. Conclusions: Our results elucidate unknown mechanisms for how PHD inhibition improves glycemic control through HIF-2α-dependent regulation of hepatic insulin and glucagon sensitivity.